Entrustable Professional Activities for Chinese Standardized Residency Training in Pediatric Intensive Care Medicine - Yun, Zhang; Jing, Liu; Junfei, Chen; Wenjing, Zhang; Jinxiang, Wu; Tong, Yue; Aijun, Zhang (Frontiers in Pediatrics, 2022)
Background Entrustable professional activities (EPAs) were first introduced by Olle ten Cate in 2005. Since then, hundreds of applications in medical research have been reported worldwide. However, few studies discuss the use of EPAs for residency training in pediatric intensive care medicine. We conducted a pilot study of EPA for pediatric intensive care medicine to evaluate the use of EPAs in this subspecialty. Materials and Methods A cross-sectional study was implemented in pediatric intensive care medicine standardized residency training at the Qilu Hospital of Shandong University. An electronic survey assessing EPA performance using eight scales composed of 15 categories were distributed among residents and directors. Results A total of 217 director-assessment and 44 residents’ self-assessment questionnaires were collected, both demonstrating a rising trend in scores across postgraduate years. There were significant differences in PGY1-vs.-PGY2 and PGY1-vs.-PGY3 director-assessment scores, while there were no differences in PGY2-vs.-PGY3 scores. PGY had a significant effect on the score of each EPA, while position significantly affected the scores of all EPAs except for EPA1 (Admit a patient) and EPA2 (Select and interpret auxiliary examinations). Gender only significantly affected the scores of EPA6 (Report a case), EPA12 (Perform health education), and EPA13 (Inform bad news). Conclusion This study indicates that EPA assessments have a certain discriminating capability among different PGYs in Chinese standardized residency training in pediatric intensive care medicine. Postgraduate year, gender, and resident position affected EPA scores to a certain extent. Given the inconsistency between resident-assessed and director-assessed scores, an improved feedback program is needed in the future.